Understanding Consumer Minds: How Psychological Aspects Drive E-commerce Purchases - Mulyadi, Rangga Dhimas Radithya; Efawati, Yen (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aims to analyze the influence of psychological factors such as motivation, perception, learning, and beliefs and attitudes on consumer purchasing decisions on e-commerce platforms, particularly focusing on the unique behaviors of young, tech-savvy consumers in the Greater Bandung area, Indonesia. The research method employs a quantitative approach with a structured questionnaire for data collection. The sample consists of 104 students who have actively engaged with e-commerce platforms, offering insights into the specific motivations driving their online shopping habits. Descriptive analysis and simple regression were utilized to examine the relationship between psychological factors and consumer purchasing decisions. The results revealed that psychological factors significantly and positively impact consumer purchasing decisions, with motivation emerging as the strongest predictor. This highlights that consumers are increasingly motivated to shop online due to the perceived convenience, comfort, and personalized experiences offered by e-commerce platforms. By understanding these psychological drivers, entrepreneurs can design tailored business strategies that enhance customer satisfaction and foster long-term loyalty, addressing the growing demand for seamless digital shopping experiences in the modern retail landscape.